(untitled) (MMIT Proceedings, 2024)
In this article, convenient and modern pedagogical technologies for teaching the marketing science, ways of their effective application and correct placement in practice are described in detail. Knowledge of marketing analysis, providing marketing with information, working with targets, positioning, development of communication tools in computer technologies, etc., is explained in brief theoretical, statistical and analytical data using tables and graphs.